2017
DOI: 10.14744/phd.2017.95967
|View full text |Cite
|
Sign up to set email alerts
|

Determining the levels of perceived social support and psychological well being of nursing students.

Abstract: Objectives:The objective of this study is to determine the levels of perceived social support and psychological well being of nursing students. Methods:The research sample for the study which is of a descriptive nature was comprised of 300 nursing students who were continuing their education during the academic year 2015-2016. 'Introductory Information Form' , 'Perceived Social Support Scale' and 'Psychological Wellbeing Scale (Short Form)' were applied as data collection tools. Kruskal Wallis, Mann Whitney U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 11 publications
2
16
0
1
Order By: Relevance
“…According to He et al, in coping with these stressors, the predictors of psychological well‐being among undergraduate nursing students include internal factors such as self‐efficacy, resilience, and mindfulness, as well as external factors such as social support. Some studies focusing on psychological well‐being have reported that well‐being is associated with resilience, self‐esteem, behavioral and affect‐focused strategies, family cohesion and social support …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to He et al, in coping with these stressors, the predictors of psychological well‐being among undergraduate nursing students include internal factors such as self‐efficacy, resilience, and mindfulness, as well as external factors such as social support. Some studies focusing on psychological well‐being have reported that well‐being is associated with resilience, self‐esteem, behavioral and affect‐focused strategies, family cohesion and social support …”
Section: Introductionmentioning
confidence: 99%
“…Some studies focusing on psychological well-being have reported that well-being is associated with resilience, self-esteem, behavioral and affect-focused strategies, family cohesion and social support. [9][10][11] Ratanasiripong and Wang, 7 in their study assessed students' wellbeing using the Rosenberg self-esteem scale, the Center for Epidemiology Studies-Depression Scale Satisfaction with Life Scale, and the Revised Cheek and Buss Shyness Scale. They found that compared with students who were recruited from a comprehensive college with degree programs in education, arts, sciences, technology, and management, nursing students had higher levels of self-esteem and life satisfaction and that they reported lower levels of depression and social difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…In the research studies on perceived social support in the literature, perceived social support and its subscales were found positive significantly related to psychological well-being and psychological resilience [21], psychological well-being [22], forgiveness of self and situations [23], self-esteem [24] and perceived social support was found negative significantly related to loneliness [25]; [26], problematic Internet use [27], parental recognition-rejection [23], and constant anger [24]. While some studies addressing the perceived social support by the gender variable showed that perceived social support was significantly high among men [28]; [19], others concluded that it was significantly higher among girls [29].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies addressing the perceived social support by the gender variable showed that perceived social support was significantly high among men [28]; [19], others concluded that it was significantly higher among girls [29]. There are also studies concluding that perceived social support did not differ significantly [30]; [22]; [31]. As can be seen from the results of the researches, social support has a very important place in the life of the individuals.…”
Section: Introductionmentioning
confidence: 99%
“…According to Aydın, Kahraman and Hiçdurmaz (2017), the increase in perceived social support positively affects the individual's overcome with stress, one's thoughts about occupation life and feeling psychologically strong. It is thought that this situation will positively affect the academic development and emotional mood on risky individuals.…”
Section: Introductionmentioning
confidence: 99%